Evidence for a Retinal Progenitor Cell in the Postnatal and Adult Mouse - Chen, Xi (Stem Cell Res, 2017)
Progress in cell therapy for retinal disorders has been challenging. Recognized retinal progenitors are a heterogeneous population of cells that lack surface markers for the isolation of live cells for clinical implementation. In the present application, our objective was to use the stem cell factor receptor c-Kit (CD117), a surface marker, to isolate and evaluate a distinct progenitor cell population from retinas of postnatal and adult mice. Here we report that, by combining traditional methods with fate mapping, we have identified a c-Kit-positive (c-Kit(+)) retinal progenitor cell (RPC) that is self-renewing and clonogenic in vitro, and capable of generating many cell types in vitro and in vivo. Based on cell lineage tracing, significant subpopulations of photoreceptors in the outer nuclear layer and bipolar, horizontal, amacrine and Müller cells in the inner nuclear layer are the progeny of c-Kit(+) cells in vivo. The RPC progeny contributes to retinal neurons and glial cells, which are responsible for the conversion of light into visual signals. The ability to isolate and expand in vitro live c-Kit(+) RPCs makes them a future therapeutic option for retinal diseases.